Short-course oral steroids as an adjunct therapy for chronic rhinosinusitis - Head, Karen; Chong, Lee Yee; Hopkins, Claire; Philpott, Carl; Schilder, Anne G M; Burton, Martin J (Cochrane database of systematic reviews, 2016)
This review is one of a suite of six Cochrane reviews looking at the primary medical management options for patients with chronic rhinosinusitis.Chronic rhinosinusitis is a common condition involving inflammation of the lining of the nose and paranasal sinuses. It is characterised by nasal blockage and nasal discharge, facial pressure/pain and loss of sense of smell. The condition can occur with or without nasal polyps. Oral corticosteroids are used to control the inflammatory response and improve symptoms. To assess the effects of a short course of oral corticosteroids as an adjunct ('add-on') therapy in people with chronic rhinosinusitis who are already on standard treatments. The Cochrane ENT Information Specialist searched the Cochrane ENT Trials Register; Central Register of Controlled Trials (CENTRAL 2015, Issue 7); MEDLINE; EMBASE; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 11 August 2015. Randomised controlled trials (RCTs) comparing a short course (up to 21 days) of oral corticosteroids to placebo or no treatment, where all patients were also receiving pharmacological treatment for chronic rhinosinusitis. We used the standard methodological procedures expected by Cochrane. Our primary outcomes were disease-specific health-related quality of life (HRQL), patient-reported disease severity, and the adverse event of mood or behavioural disturbances. Secondary outcomes included general HRQL, endoscopic nasal polyp score, computerised tomography (CT) scan score, and the adverse events of insomnia, gastrointestinal disturbances and osteoporosis. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. Two trials with a total of 78 participants met the inclusion criteria. Both the populations and the 'standard' treatments differed in the two studies. Oral steroids as an adjunct to intranasal corticosteroids One trial in adults with nasal polyps included 30 participants. All participants used intranasal corticosteroids and were randomised to either short-course oral steroids (oral methylprednisolone, 1 mg/kg and reduced progressively over a 21-day treatment course) or no additional treatment. None of the primary outcome measures of interest in this review were reported by the study. There may have been an important reduction in the size of the polyps (measured by the nasal polyps score, a secondary outcome measure) in patients receiving oral steroids and intranasal corticosteroids, compared to intranasal corticosteroids alone (mean difference (MD) -0.46, 95% confidence interval (CI) -0.87 to -0.05; 30 participants; scale 1 to 4) at the end of treatment (21 days). This corresponds to a large effect size, but we are very uncertain about this estimate as we judged the study to be at high risk of bias. Moreover, longer-term data were not available and the other outcomes of interest were not reported. Oral steroids as an adjunct to antibiotics One trial in children (mean age of eight years) without nasal polyps included 48 participants. The trial compared oral corticosteroids (oral methylprednisolone, 1 mg/kg and reduced progressively over a 15-day treatment course) with placebo in participants who also received a 30-day course of antibiotics. This study addressed one of the primary outcome measures (disease severity) and one secondary outcome (CT score). For disease severity the four key symptoms used to define chronic rhinosinusitis in children (nasal blockage, nasal discharge, facial pressure, cough) were combined into one score. There was a greater improvement in symptom severity 30 days after the start of treatment in patients who received oral steroids and antibiotics compared with placebo and antibiotics (MD -7.10, 95% CI -9.59 to -4.61; 45 participants; scale 0 to 40). The observed mean difference corresponds to a large effect size. At the same time point there was a difference in CT scan score (MD -2.90, 95% CI -4.91 to -0.89; 45 participants; scale 0 to 24). We assessed the quality of the evidence to be low.There were no data available for the longer term (three months). There might be an improvement in symptom severity, polyps size and condition of the sinuses when assessed using CT scans in patients taking oral corticosteroids when these are used as an adjunct therapy to antibiotics or intranasal corticosteroids, but the quality of the evidence supporting this is low or very low (we are uncertain about the effect estimate; the true effect may be substantially different from the estimate of the effect). It is unclear whether the benefits of oral corticosteroids as an adjunct therapy are sustained beyond the short follow-up period reported (up to 30 days), as no longer-term data were available.There were no data in this review about the adverse effects associated with short courses of oral corticosteroids as an adjunct therapy.More research in this area, particularly research evaluating longer-term outcomes and adverse effects, is required.